PENGARUH PEMBERIAN PUPUK BOKASHI KOTORAN WALET TERHADAP KESUBURAN TANAH PADA TANAMAN JAHE MERAH (Zingiber officinable rosc) DI KECAMATAN TINOMBO KABUPATEN PARIGI MAUTONG - Ramlan Ramlan; Risman Risman (Fakultas Pertanian, Universitas Tadulako, 2022)
Soil quality improvement can be done by adding organic fertilizer one of them is swallow guano. This study aim was to determine the effect of swallow guano bokashi on soil chemical characteristics and the growth of red ginger plants. The guano bokashi was applied at various rates i.e., no guano added (BW0), 10 t guano ha-1 (BW1), 20 t guano/ha-1 (BW2) and 30 t guano/ha-1 (BW3). Plant height, leaf number and fresh weight of ginger root increased with increasing the guano bokashi rates both at 30 days after planting (DAP) and 60 DAP. Soil analysis showed that the lowest pH (7.01), C-organic (0.72%), N-total (0.11%), P2O5 (52.16 mg 100 g-1), K2O (41.10 mg 100 g-1), and CEC (13.91 cmol (+) kg-1) was found in the BW0 treatment whereas the highest pH (7.39), C-organic (1.43%), N-total (0.20%), P2O5 (61.82 mg 100 g-1), K2O (46.69 mg 100 g-1), and CEC (19.11 cmol (+) kg-1) was found in the BW3 treatment.